Sociocultural Studies in Harmony Interfaith based Bali Local Wisdom - Kiriana, I Nyoman; Dasih, I Gusti Ayu Ratna Pramesti; Widiasih, Ni Nyoman Sri; Supandi, I Nyoman Alit; Sujana, I Wayan (Journal of Ecohumanism, 2024)
Denpasar City, the capital of Indonesia's Bali Province and famous for its international tourist destinations, is strategically located, making it a target for urbanisation worldwide. Multicultural life is a common sight in Denpasar City, where various ethnicities, religions and cultures develop into a unity in society. Inter-religious harmony is an important concern in multicultural life, because various problems will arise including conflict. Inter-religious harmony in Denpasar City is harmonious because of the people's belief in Balinese local wisdom that surrounds their social interactions. Balinese local wisdom is used as the basis for social interaction in the lives of the people of Denpasar City, so the purpose of this study is to explore the values of Balinese local wisdom as the basis for religious harmony in Denpasar City seen from the challenges and strategies. This research uses qualitative methods with sociocultural mapping, with direct researcher involvement in data collection through in-depth interviews and dialogue according to the experience of informants. The technique of determining informants using purposive sampling, then the analysis is carried out with data triangulation such as data collection, reduction, and conclusion drawing. The results of this study reveal that inter-religious harmony in Denpasar City involves the role of Balinese local wisdom as a social foundation for the community. Balinese local wisdom is believed to contain social values that are upheld by the community as social capital in interaction, such as: the philosophy of Tri Hita Karana, Tri Kaya Parisudha, Tat Twam Asi, and the philosophy of menyama braya. Inter-religious harmony in Denpasar City is harmonious based on the awareness of the community to maintain, respect, and appreciate each other so as to create harmony of social interaction.